Analisis Distribusi Pemasaran Udang Windu (Penaeus monodon) di Kelurahan Margomulyo, Kecamatan Balikpapan Barat Kota Balikpapan - Abdul Hadi Bone (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2018)
Margomulyo area is a protected area that provides various benefits to support life for the community. This study aims to determine: (i) the number of marketing institutions in the distribution of marketing of tiger shrimp, (ii) the marketing channels available in the marketing of tiger shrimp by pond farmers in Margomulyo Village, Balikpapan Barat District, Balikpapan City, (iii) marketing margins in the distribution of black shrimp marketing. This research was carried out in Margomulyo area in September-December 2016. The research method used a field survey method by interviewing fishing communities and literature. To analyze marketing functions, it is analyzed based on the functions of each marketing agency, while the analysis of margin distribution is done by calculating marketing costs both at the consumer and producer level. The results of the study of marketing patterns of freckle shrimp in the Margomulyo Region indicate that there are four patterns of marketing distribution channels, namely: I (producer-consumer), II (consumer-retailer), III (producer-retailer-consumer) and IV (producer-gatherer) -customer-sellers-retailers). The marketing distribution of tiger shrimp on pattern channel II (Producers-Retailers-Consumers) is more dominantly used because the marketing distribution channel is relatively shorter so it cuts the marketing distribution flow to the final consumer level, so it can suppress other additional costs. This can be seen based on the value of the share obtained at 75.05%, the selling price of tiger shrimp in the final consumer is 37,000, while the average selling price is Rp. 27,767, - Marketing margin of Rp. 9,233, - with a profit of 5,881. This value shows the advantages for the promising shrimp producer (producer) farmers as the main business actors of tiger shrimp cultivation